Ogólnopolska Interdyscyplinarna Konferencja Naukowa „Życie bez miłości jest (nie)możliwe” - Kopeć, Urszula (Dydaktyka Polonistyczna, 2018)
On 24th and 25th of May, 2018, the Institute of Polish Studies and Journalism of the University of Rzeszów hosted the scientific conference Life without Love is (not) possible. The conference was organized by the employees of the Department of Methodology of Teaching Literature and Polish Language. Over forty participants from the most important academic centres from all over Poland took part in it. The speakers addressed not only general topics concerning basic types of love (agape, charis, eros, family), but also referred to more detailed, but extremely important issues, such as: aspects, features of this value depicted in literary texts, magazines or aphorisms; ways of talking about love in the statements of young people and school textbooks.